Optimizing Science Literacy Through the Implementation of STEM in the Physical Education Curriculum in Kediri City - Nur Ahmad Muharram; Agung Pratama, Budiman; Weda; Entin Srihadi Yanti; Imam Sugeng; Reo Prasetiyo Herpandika; Rendhitya Prima Putra (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Increasing scientific literacy in the Industrial Revolution 4.0 era is a must. Scientific literacy is a skill that is very necessary in the 21st century, so it is important to improve it through various strategies. One effective strategy is innovative learning with a STEM (Science, Technology, Engineering, and Mathematics) approach, which integrates science, technology, engineering and mathematics in the learning process. This research involved samples from the Subject Teachers' Conference (MGMP) at the elementary, middle and high school levels in Kediri City to analyze the effectiveness of STEM-based learning in increasing scientific literacy. This article is a literature review that discusses the relationship between scientific literacy and the competencies needed in the Industrial Revolution 4.0 era, as well as how the STEM approach can be a solution in increasing scientific literacy